Psychiatry: bioethics – insanity and (un)humanization - José Raimundo Evangelista da Costa (O Mundo da Saúde, 2010)
This paper aims to address the issue of psychiatry and of (un) humanization when bioethics is not present in the psychiatric environment. Will present the case of a psychiatric hospital that was closed by the mistreatment and cruelty with which their patients were treated. We believe we have a responsibility to change the situation of mental health and psychiatry and we must never blame others because of the change is not possible, because it also depends on each one of us. We will also approach the unbearable raised by madness and the urgency to humanize the practice and care in psychiatry.